87.0k views
0 votes
2(x + 3) – 10 = 4x


Can you also explain please. Thanks

2 Answers

3 votes

Answer:

x = -2

Explanation:

First distribute the 2 with x and 3

Equation should look like... 2x + 6 - 10 = 4x

Second combine like terms, 6 and -10

Equation should look like... 2x - 4 = 4x

Third bring 2x to the other side making it -2x and subtract it from 4x

Equation should look like... -4 = 2x

Last divide -4 and 2.

Equation should look like... x = -2

User Dimitar Marinov
by
6.1k points
5 votes

Answer:

x=-2

Explanation:

2(x+3)-10=4x

2x+6-10=4x

6-10=2x

-4=2x

-2=x

User Kerryann
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.